Sensitivity and Specificity of the Modified Epworth Sleepiness Scale in Children With Craniopharyngioma - Crabtree, Valerie McLaughlin (J Clin Sleep Med, 2019)
STUDY OBJECTIVES: Children with craniopharyngioma are at risk for excessive daytime sleepiness (EDS). Multiple Sleep Latency Testing (MSLT) is the gold standard for objective evaluation of EDS; however, it is time and resource intensive. We compared the reliability, sensitivity, and specificity of the modified Epworth Sleepiness Scale (M-ESS) and MSLT in monitoring EDS in children with craniopharyngioma. METHODS: Seventy patients (ages 6 to 20 years) with craniopharyngioma completed the M-ESS and were evaluated by polysomnography and MSLT. Evaluations were made after surgery, if performed, and before proton therapy. RESULTS: MSLT revealed that 66 participants (81.8%) had EDS, as defined by a mean sleep latency (MSL) < 10 minutes, with only 28.8% reporting EDS on the M-ESS by using a cutoff score of 10. The M-ESS demonstrated adequate internal consistency and specificity (91.7%) but poor sensitivity (33.3%) with the established cutoff score of 10. A cutoff score of 6 improved the sensitivity to 64.8% but decreased the specificity to 66.7%. CONCLUSIONS: Patients with craniopharyngioma are at high risk for EDS, as documented objectively on the MSLT, but they frequently do not recognize or accurately report their sleepiness. Future sleep studies should investigate whether specific items or alternative self- and parent-reported measures of sleepiness may have greater clinical utility in monitoring sleepiness in this population. CITATION: Crabtree VM, Klages KL, Sykes A, Wise MS, Lu Z, Indelicato D, Merchant TE, Avent Y, Mandrell BN. Sensitivity and specificity of the modified Epworth Sleepiness Scale in children with craniopharyngioma. J Clin Sleep Med. 2019;15(10):1487–1493.